THEORETICAL AND METHODOLOGICAL PRINCIPLES FOR SOCIAL WORKERS TO PROMOTE SCIENTIFIC RESEARCH - А. Конончук (Київський національний університет імені Тараса Шевченка, 2016)
Article grounded theoretical background training of social workers in research in the context of basic professional functions as a prerequisite for raising their professional competence. These author includes general information on: the nature and methods of scientific knowledge of objective reality, the object and the subject of scientific knowledge; concept of scientific research (fundamental and applied) as the main form of exercise science and scientific development; basic methods of empirical and theoretical research; integrated approach to scientific research; systematic and consistent diagnostic activities; the structure of the process of scientific research and general description of its main stages; unity of theory and practice in scientific knowledge; the role of practice as the basis of knowledge and truth criterion in assessing the consequences of money.Analyzed the nature of research and prognostic functions of social workers in professional activities. Identify features of research in the field of social work, namely complexity; purposefulness; interrelation of all elements, processes and technologies; subjective-subjective nature; complexity and scale of social problems; available resources; the timing of. Relationships revealed features of social studies of general approaches to research, including content described their tasks, functions and stages.

У статті обґрунтовуються теоретичні засади професійної підготовки соціальних працівників до наукових досліджень у контексті здійснення базових професійних функцій як необхідної умови підвищення рівня їх професійної компетентності. Аналізується сутність дослідницької та прогностичної функції соціального працівника у професійній діяльності. Визначаються особливості наукових досліджень у сфері соціальної роботи. Розкриваються взаємозв'язки особливостей соціальних досліджень із загальними підходами до наукових досліджень, зокрема, змістовно охарактеризовано їх задачі, функції, етапи.
ТЕОРЕТИКО-МЕТОДОЛОГІЧНІ ЗАСАДИ ПІДГОТОВКИ СОЦІАЛЬНИХ ПРАЦІВНИКІВ ДО ПРОВЕДЕННЯ НАУКОВИХ ДОСЛІДЖЕНЬ
Keywords: професійна підготовка; соціальний працівник; соціальна проблема; діагностична функція; прогностична функція; наукове дослідження; соціальне дослідження; vocational training; social worker; social problem; a diagnostic function; predictive function; scientific research; social studies